What next? Towards an agenda for classroom codeswitching research - Ferguson, Gibson (International journal of bilingual education and bilingualism, 2009)
In this issue, aside from the introduction, there are six papers on classroom code-switching (CS), covering a wide spectrum of geographic and pedagogic contexts: two from Africa focussing on switching in content subject lessons; two from Taiwan looking at CS in EFL language subject classrooms; and two further papers, one looking at written CS and another exploring CS in UK complementary schools. Diverse though the settings covered may be, they are unified by a shared focus on the pedagogic functions of classroom CS and by a common interest in attitudes to CS, particularly on the part of educational authorities and teachers. This author makes two methodological points on the topic of functions: (1) how functions of classroom CS come to be individuated and identified; and (2) the treatment of CS as a linguistically relatively undifferentiated phenomenon. This article ends with a summary list of suggestions for further classroom-related CS research. (Contains 2 notes.)